2020
DOI: 10.1139/apnm-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Addition of pectin-alginate to a carbohydrate beverage does not maintain gastrointestinal barrier function during exercise in hot-humid conditions better than carbohydrate ingestion alone

Abstract: Purpose: To compare the effects of consuming a 16% maltodextrin+fructose+pectin alginate (MAL+FRU+PEC+ALG) drink against a nutrient matched maltodextrin-fructose (MAL+FRU) drink on enterocyte damage and gastrointestinal permeability after cycling in hot and humid conditions. Methods: Fourteen recreational cyclists (7 men) completed three experimental trials in a randomized placebo-controlled design. Participants cycled for 90 min (45% VO2max) and completed a 15 min time-trial in hot (32°C) humid (70% relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…Mears et al (2020b) and Baur et al (2019) found no differences in relative substrate contribution during submaximal cycling at 50% W max but the nonsignificant increase in fat oxidation (and decrease in CHO oxidation) reported by Baur et al (2019) is notable, and consistent with Barber et al (2020). Flood et al (2020) also reported similar CHO and fat oxidation with CHO and hydrogel ingestion during low-intensity cycling. However, Baur et al (2019) also noted lower absolute total CHO and fat (to Mears et al [2020b] in both conditions), despite similar ingestion rates (68 and 78 g.hr -1 ).…”
Section: Physiological Measuressupporting
confidence: 56%
See 3 more Smart Citations
“…Mears et al (2020b) and Baur et al (2019) found no differences in relative substrate contribution during submaximal cycling at 50% W max but the nonsignificant increase in fat oxidation (and decrease in CHO oxidation) reported by Baur et al (2019) is notable, and consistent with Barber et al (2020). Flood et al (2020) also reported similar CHO and fat oxidation with CHO and hydrogel ingestion during low-intensity cycling. However, Baur et al (2019) also noted lower absolute total CHO and fat (to Mears et al [2020b] in both conditions), despite similar ingestion rates (68 and 78 g.hr -1 ).…”
Section: Physiological Measuressupporting
confidence: 56%
“…Performance was similar with MD + F hydrogel, isocaloric MD + F fluids (Figure 3; Baur et al, 2019;Flood et al, 2020;McCubbin et al, 2019;Mears et al, 2020b), or noncaloric hydrogel (Pettersson et al, 2019). Relative performance changes between CHO hydrogel and fluids ranged between +1.05% and +3.8% but were not statistically significant (p < .05).…”
Section: Exercise Performancementioning
confidence: 80%
See 2 more Smart Citations
“…This finding is in accord with a recent study where ingestion of a 500 mL bolus of a 18% carbohydrate drink containing 0.4 g pectin and 0.6 g of alginate resulted in 1.8 and 2.4 times faster gastric half-emptying time compared to an isoenergetic MD+FRU drink and a glucose+FRU drink, respectively (42). Recent studies have found no difference in total substrate oxidation and blood glucose concentrations (43)(44)(45) or exogenous carbohydrate oxidation (46) with the addition of sodium alginate and pectin in drinks matched for maltodextrin and fructose content during exercise.…”
Section: Exogenous Carbohydrate Oxidationsupporting
confidence: 90%